(untitled) (CIPEEX, 2025)
This article analyzes the legal nature of decisions that recognize tax immunity and argues for their declaratory character, with retroactive effects (ex tunc) to the moment the constitutional and statutory requirements for the benefit were met. The objective is to identify the normative and case-law foundations of such retroactivity and to map its practical consequences for tax enforceability, assessment, refunds of undue payments, and the applicability of penalties and interest. The method is doctrinal and case-law based, examining the Federal Constitution and the National Tax Code, as well as higher-court precedents, and distinguishing tax immunity - understood as a constitutional limitation on taxing power - from exemptions and non-incidence. The findings indicate that immunity operates as a negative rule of competence: immune facts or taxpayers lie outside the taxable field, so judicial or administrative decisions merely declare a preexisting situation; it follows that tax credits asserted after the requirements were fulfilled are unenforceable, taxpayers are entitled to refunds of amounts unduly collected, and penalties tied to default do not apply. It concludes that embracing the declaratory nature of immunity, together with standardized administrative procedures to verify the requirements and due regard to any effect-modulation by the Supreme Court, enhances legal certainty, prevents unconstitutional collection, and streamlines refunds, thereby preserving systemic coherence.